Serum neutrophil gelatinase-associated lipocalin and resistin are associated with dengue infection in adults. Issue 1 (December 2016) - Liu, Kuan-Ting; Liu, Yao-Hua; Lin, Chun-Yu; Tsai, Ming-Ju; Hsu, Ya-Ling; Yen, Meng-Chi; Kuo, Po-Lin
Abstract Background Dengue is a major health problem in tropical areas, including Taiwan. Dengue virus infection affects various types of cells and results in elevation of serum inflammatory molecules. Because these molecules may be associated with dengue virus infection, the aim of this study was to identify novel molecules in febrile patients with dengue infection. In addition, we determined whether these molecules were correlated with the count of leukocytes and platelets. Methods Febrile adults (Age >18 years old) who presented to the emergency department and were confirmed dengue virus infection were enrolled in this study. Serum from dengue patients and healthy controls was collected and serum level of sepsis-associated inflammatory molecules was measured by Luminex assay. Results Elevated level of macrophage migration inhibitory factor, soluble vascular cell adhesion molecule-1, sFasL, resistin and interferon-γ were detected in patients' serum. Higher levels of neutrophil gelatinase-associated lipocalin (NGAL) and resistin were detected in dengue patients with normal leukocyte count and all dengue patients, respectively. Furthermore, the serum level of NGAL, but not resistin, was correlated with cell count in dengue patients. Conclusion Our results revealed that resistin and NGAL are novel dengue-associated molecules. These results may help elucidate the regulatory mechanisms of anti-dengue immune responses.